2021
DOI: 10.3390/jof7050377
|View full text |Cite
|
Sign up to set email alerts
|

The Known Unknowns of the Immune Response to Coccidioides

Abstract: Coccidioidomycosis, otherwise known as Valley Fever, is caused by the dimorphic fungi Coccidioides immitis and C. posadasii. While most clinical cases present with self-limiting pulmonary infection, dissemination of Coccidioides spp. results in prolonged treatment and portends higher mortality rates. While the structure, genome, and niches for Coccidioides have provided some insight into the pathogenesis of disease, the underlying immunological mechanisms of clearance or inability to contain the infection in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 138 publications
(167 reference statements)
0
5
0
1
Order By: Relevance
“…Pulmonary epithelial cells interact with the arthroconidia very early in the course of infection. There have been some fascinating hypotheses about the importance of this interaction, but no data have been published [ 12 ]. Recently, Hsu reported that mutations in Duox1, a lung epithelial cell oxidase that generates H 2 O 2 , were more common in patients with disseminated coccidioidomycosis than in the general population, suggesting that this enzyme plays a role in innate resistance to coccidioidomycosis [ 13 ].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Pulmonary epithelial cells interact with the arthroconidia very early in the course of infection. There have been some fascinating hypotheses about the importance of this interaction, but no data have been published [ 12 ]. Recently, Hsu reported that mutations in Duox1, a lung epithelial cell oxidase that generates H 2 O 2 , were more common in patients with disseminated coccidioidomycosis than in the general population, suggesting that this enzyme plays a role in innate resistance to coccidioidomycosis [ 13 ].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Coccidioidomycosis or Valley Fever is caused by species of dimorphic fungus, Coccidioides , a major cause of mycosis endemic to the southwestern United States. Immunity to Valley Fever is primarily associated with T cells expressing both type 1 and type 17 cytokines (Th1/Th17) ( 179 , 180 ). The regulatory T cells were associated with persistent coccidioidomycosis in the pediatric population that was recapitulated in resistant vs. susceptible mice ( 181 , 182 ).…”
Section: Pathogen-specific Antifungal T Cellsmentioning
confidence: 99%
“…The latter includes for example, viral infections with: adenoviruses “in immunocompetent individuals” 4 ; dengue virus 5 ; hepatitis E virus 6 ; herpes simplex virus type 1 in “the acute infection state but not the latent infection state” 7 ; human papilloma virus 8 ; and West Nile virus 9 . Furthermore, it also includes bacterial infection with Coxiella burnetii in animals, 10 fungal infection with Coccidioides immitis and C. posadasii , 11 and parasitic infection with the protozoan Giardia duodenalis 12 …”
Section: Introductionmentioning
confidence: 99%
“…virus. 9 Furthermore, it also includes bacterial infection with Coxiella burnetii in animals, 10 fungal infection with Coccidioides immitis and C. posadasii, 11 and parasitic infection with the protozoan Giardia duodenalis. 12 As a matter of fact, an aberrant and/or dysfunctional/defective innate immune response during the early phases of an infection or upon encountering unwanted foreign particles/substances may be the leading cause of disease severity.…”
mentioning
confidence: 99%